Development of Toupic (Touch Picture) Applications to Improve Expressive Language in Speech-Delayed Children - Mirnawati Mirnawati; Rizkia Ilahiah (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aims to develop a product in the form of a toupic (touch picture) application to help stimulate the increase of expressive language in children with speech delay. This type of research is Research and Development (RD) using the ADDIE model (analysis, design, development, implementation, and evaluation). This research was conducted at SLB Negeri 1 Martapura, South Kalimantan. Data collection techniques using interviews, tests and questionnaires. interviews are used to get an overview of needs analysis data and product evaluation by users. The test is used to measure speech delay children's expressive language skills in the initial and final conditions after using the product. while the angle is used to measure the level of product validation by the validator. Qualitative data from interviews were analyzed descriptively while quantitative data from tests and questionnaires were analyzed using statistics with the formula P=(∑R)/N X 100%. The development of the toupic application goes through several stages, namely: 1) the analysis stage as an initial research to determine the conditions and needs of children, 2) the design stage is carried out by compiling a conceptual framework for application development, 3) the development stage, namely developing an application framework by information and technology experts who then validated by experts with a validation percentage of 95% and declared very valid, 4) the implementation stage to test the toupic (touch picture) application on speech delay children with a result of 82%, and 5) the evaluation stage showed an increase in the expressive language skills of speech delay children. from the percentage of results before and after that is 52% to 82% indicates that the application does not require final revision anymore. Thus it can be concluded that the development of the toupic application (touch picture) can improve the expressive language skills of speech delay children.